Hacia el origen de la intencionalidad. La búsqueda de una primigeneidad en Husserl, Henry y Marion - Marenghi, Claudio (2022)
The intentional correlation between the consciousness and the world is the central theme of phenomenology. Edmund Husserl has attempted to found this correlation by making explicit a previous passive vital course, teleologically oriented towards intentional activities. In this same task, Michel Henry has accentuated the pole of the immanence of correlation, founding the intentionality of consciousness in affective life. For their part, Jean-Luc Marion has emphasized the pole of the transcendence of correlation and has decentered the intentionality of consciousness, attending to the saturation of phenomena. In this work we intend to briefly go through the three paths indicated in search of the original proto-phenomenon of the experience, trying to contrast the proposals and glimpse possible convergences.